RSA-based image recognizable adversarial attack method - Yu ZHANG; Hailiang LI (网络与信息安全学报)
Adversarial attack is an important part of deep learning security research.Relying on the RSA signature schemes and RSA encryption schemes in cryptography, an adversarial attack method that adversarial examples can be recognized by a specific classifier is proposed.Through the idea of one pixel attack, the normal image can have the ability to make other classifier misclassify while embedding additional information.It can be used in classifier authorization management, online image anti-counterfeiting, etc.The experiment show that the adversarial examples can be recognized under the specific classifier, and the disturbance noise is difficult to detect by the human eye.